Interactions in the marine benthos global patterns and processes - Bohn, Katrin; Firth, Louise B.; Hawkins, S. J.; Williams, Gray A. (Cambridge University Press, 2019)
The synthesis of the Aquatic Biodiversity and Ecosystems Conference (ABEC) 2015, which was held to assess scientific progress over the past twnety-five years, this book provides a comprehensive and global review of work since the 1992 publication of Plant-Animal Interactions in the Marine Benthos. Taking a regional and, where appropriate, habitat perspective, it considers sites of coastal biodiversity from around the world to incorporate a global approach. The volume analyses abiotic and biotic interactions, and the factors determining distribution patterns, community structure and ecosystem functioning of coastal systems. It explores themes of how phylogeography and biogeographic process influence assemblage composition, and hence drive community structure and the respective roles of environmental factors and biological interactions, with the overall goal to establish how general are the processes in different regions and habitats. For researchers, graduate students and academics studying coastal ecosystems, with interest for conservation practitioners managing areas of high biodiversity.